2014
DOI: 10.1074/jbc.m113.544494
|View full text |Cite
|
Sign up to set email alerts
|

Activated Hepatic Stellate Cells Are Dependent on Self-collagen, Cleaved by Membrane Type 1 Matrix Metalloproteinase for Their Growth

Abstract: Background:The mechanisms of apoptosis induced by antifibrosis therapy in activated hepatic stellate cells (aHSCs), the main collagen producer in cirrhotic livers, are unknown. Results: aHSCs underwent apoptosis by inhibiting the supply of membrane type 1 matrix metalloproteinase (MT1-MMP)-cleaved collagen. Conclusion: aHSCs require MT1-MMP-cleaved collagen for their survival. Significance: Interference with the supply of MT1-MMP-cleaved collagen for aHSCs is a reasonable antifibrosis strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…In this regard, it may be an interesting challenge to explore the possibility in the future that MT1-MMP cleaved collagen from aPSCs stimulates replication of PACs in a paracrine manner, since our previous observation clearly demonstrated that collagen secreted from activated hepatic stellate cells (aHSCs) sustains their own survival in an autocrine manner after it is cleaved by membrane type1 metalloproteinase (MT1-MMP) [25]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, it may be an interesting challenge to explore the possibility in the future that MT1-MMP cleaved collagen from aPSCs stimulates replication of PACs in a paracrine manner, since our previous observation clearly demonstrated that collagen secreted from activated hepatic stellate cells (aHSCs) sustains their own survival in an autocrine manner after it is cleaved by membrane type1 metalloproteinase (MT1-MMP) [25]. …”
Section: Discussionmentioning
confidence: 99%
“…The PSCs were transfected with siRNA HSP47 with the same the method as applied for hepatic stellate cells [24,25]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Also, MT1-MMP participates in the regulation of fibrosis progression as it cleaves intramolecular RGD motifs of collagen produced by activated HSCs and thus controls aVβ1 activation, providing a survival signal via PI3K/AKT/IκB. 69 During the entire progress of liver fibrosis, the expression of main inhibitor of MMPs, TIMP-1, is increased to regulate the elevated MMP activity. TIMP-1 has distinct functions in establishment and resolution of fibrosis.…”
mentioning
confidence: 99%
“…The most basic biological functionality in using two-dimensional (2D) cultures in combination with ECM is achieved by addition of the commonly used Arg-Gly-Asp (RGD) peptide as cell-adhesive ligands. Until today, the RGD peptide is a known adhesive domain of several ECM components, such as that involved in the binding of fibronectin [48], an important assembler of the collagen matrix, to the α5β1 integrin receptor [49] with the presence of the intra-molecular RGD motifs in collagen [50].…”
Section: Single Cell Culture and 2d: Importance Of Adhesion Arg-gly-mentioning
confidence: 99%